The Cosmic Ultraviolet Baryon Survey (CUBS) – I. Overview and the diverse environments of Lyman limit systems at z < 1. Issue 1 (17th June 2020) - Chen, Hsiao-Wen; Zahedy, Fakhri S; Boettcher, Erin; Cooper, Thomas M; Johnson, Sean D; Rudie, Gwen C; Chen, Mandy C; Walth, Gregory L; Cantalupo, Sebastiano; Cooksey, Kathy L; Faucher-Giguère, Claude-André; Greene, Jenny E; et al.
ABSTRACT: We present initial results from the Cosmic Ultraviolet Baryon Survey (CUBS). CUBS is designed to map diffuse baryonic structures at redshift z ≲ 1 using absorption-line spectroscopy of 15 UV-bright QSOs with matching deep galaxy survey data. CUBS QSOs are selected based on their NUV brightness to avoid biases against the presence of intervening Lyman limit systems (LLSs) at z abs < 1. We report five new LLSs of $\log \, N({ H \, {\small I}})/{{\rm cm^{-2}}}\gtrsim 17.2$ over a total redshift survey path-length of $Δ \, z_{ LL}=9.3$, and a number density of $n(z)=0.43_{-0.18}^{+0.26}$ . Considering all absorbers with $\log \, N({{ H \, {\small I}}})/{{\rm cm^{-2}}}\gt 16.5$ leads to $n(z)=1.08_{-0.25}^{+0.31}$ at z abs < 1. All LLSs exhibit a multicomponent structure and associated metal transitions from multiple ionization states such as C ii, C iii, Mg ii, Si ii, Si iii, and O vi absorption. Differential chemical enrichment levels as well as ionization states are directly observed across individual components in three LLSs. We present deep galaxy survey data obtained using the VLT-MUSE integral field spectrograph and the Magellan Telescopes, reaching sensitivities necessary for detecting galaxies fainter than $0.1\, L_*$ at d ≲ 300 physical kpc (pkpc) in all five fields. A diverse range of galaxy properties is seen around these LLSs, from a low-mass dwarf galaxy pair, a co-rotating gaseous halo/disc, a star-forming galaxy, a massive quiescent galaxy, to a galaxy group. The closest galaxies have projected distances ranging from d = 15 to 72 pkpc and intrinsic luminosities from ${≈} 0.01\, L_*$ to ${≈} 3\, L_*$ . Our study shows that LLSs originate in a variety of galaxy environments and trace gaseous structures with a broad range of metallicities.